Peran Pola Asuh Orang Tua Terhadap Karakter Siswa SDN 01 Kemala Raja - Putri, Kurnia Dwi; Askaf, M.Ardhian Rahali (Indo-MathEdu Intellectuals Journal, 2023)
Parenting style is the best way for parents to educate their children as an embodiment of their sense of responsibility towards their children. Islam also views the family as the first environment for an individual where he interacts or acquires the basic elements and characteristics of personality. Parents are obliged to create appropriate parenting patterns in educating their children in the family environment. This type of research is qualitative research, namely "a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. Based on data from the results of research conducted regarding the Role of Parenting Patterns on the Responsible Character of Kemala Raja Elementary School Students, the following conclusions were produced: Firstly, the parenting patterns of parents of Kemala Raja Elementary School Students are divided into two types, namely authoritarian parenting patterns and democratic parenting patterns. Second, the role of parental parenting towards the character of students at SDN Kemala Raja is as follows: Role as creator/designer, educator, role model/simulator, reactor, motivator, socialitator and evaluator.